Changes in sprint performance and kinetics during the acceleration phase of running of a world record holder - Kobayashi, K.; Tsuchie, H.; Matsuo, A.; Fukunaga, T.; Kawakami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: Previously, it was reported that faster athletes tend to produce vertical ground reaction force (GRF) impulse during the acceleration phase of sprint (Hunter et al. 2005). The purpose of this study was to investigate changes in sprint performance and kinetics during the acceleration phase of running for a world record holder. METHOD: A world record holder (A.P), 100-m best time 9.74 sec, and a Japanese Olympic athlete (N.A), 100-m best time 10.02 sec, performed several start dashes along a 100 m linear indoor track. Cinematographic recordings of sprint were made with 12 infrared cameras (VICON system; VICON Motion Systems, 120Hz), and GRF was obtained from 6 force platforms (90cm×60cm, Kisrler-9287A; Kistler, 600Hz). The markers were placed on the lateral surfaces of the joints. The center of mass was identified from the kinematic data. Running velocity was calculated by multiplying stride length (SL) and stride frequency (SF). RESULTS: During the acceleration phase, the running velocity increased that was accompanied by an increase in the SL while the SF remained unchanged in both sprinters. The SL of A.P was larger than that of N.A at every step. The vertical GRF increased with increasing running velocity, and the peak value of A.P was also larger than that of N.A at every steps. Even if the vertical GRF was divided by the body weight, the tendency was the same.